Peran Ijtihad dalam Menjawab Tantangan Hukum Islam di Era Modern - Robbi Hardiansyah Manik; Fadhil Muhammad Dzaki; Amalia Azzahra; Juanda Pramu Yudistira; Wismanto Wismanto; Fitria Mayasari (Jurnal Kajian dan Penelitian Umum, 2024)
This article discusses the role of ijtihad in responding to the challenges of Islamic law in the modern era. In the era of modernization marked by social changes, technological advances, and foreign cultural influences, Islamic law is faced with various complex challenges. This paper aims to analyze the role and function of ijtihad in facing the challenges of Islamic law in the modern era. This research aims to explore how ijtihad as a method of legal reasoning can adapt to the changing times. This research uses a qualitative approach with a literature study design to analyze the role of ijtihad in responding to the challenges of Islamic law in the modern era. Data was collected through a study of various literature including articles, journals, and relevant Islamic legal documents. Ijtihad comes from tge word “jahada” whiche means to sstrive hard. Ijtihad is a serious effort by a mujtahid to explore sharia law and its main sources, namely the al-Qur’an and hadist. When these 2 sources do not provide a clear answer, ijtihad is carried out through certain methods. In the figh tradition, there are several methods used in ijtihad such as qiyas, istihsan, mashalalha murshala, and urf. Overall, the role of ijtihad in responding to the challenges of Islamic law in the modern era is very relevant. The results of this research indicate that ijtihad plays a significant role in modern life, especially in providing solutions to contemporary problems faced by Muslims. Ijtihad can be a tool to strengthen understanding and active practice of Islamic teachings, making Islamic law remain relevant and beneficial for humanity in this modern era.